ESTABLISHING THE PARAMETERS OF THE OPERATION MODE OF THE ELECTRIC PULSE AUTOMOBILE MUFFLER - Kukesheva, Aliya; Kadyrov, Adil; Kryuchkov, Yevgeniy (Journal of Applied Engineering Science, 2024)
The purpose of the research in the article is to obtain analytical and experimental results on the purification of internal combustion engine exhaust gases by an electric pulse, allowing us to determine the main parameters of the muffler operation. The set goal was achieved by performing the following methodology. A mathematical model of the motion of a gas particle in a muffler has been developed and investigated, the relationship between the capacity of the engine combustion chamber, the number of revolutions of the crankshaft, the pulse intensity, and the dynamic viscosity of the medium has been established. The condition of the muffler operation is determined through the parameter – the distance between the electrodes. The optimality criterion is justified – the smokiness of the gas before and after purification. A nonlinear experimental plan has been compiled using the methods of similarity theory and dimension analysis. An experimental stand has been developed and results linking the process parameters have been obtained. The results obtained are the basis for the methodology for calculating the design of electric pulse mufflers with optimal smoke ratios.